Approaches to clinical guideline development in healthcare: a scoping review and document analysis - Annemarie De Leo; Dianne Bloxsome; Sara Bayes (BMC, 2023)
Abstract Background Over the past decade, an industry has emerged around Clinical Practice Guideline (CPG) development in healthcare, which has increased pressure on guideline-producing organisations to develop CPGs at an accelerated rate. These are intended to improve the quality of care provided to patients while containing healthcare costs and reducing variability in clinical practice. However, this has inadvertently led to discrepancies in CPG recommendations between health organisations, also challenging healthcare providers who rely on these for decision-making and to inform clinical care. From a global perspective, although some countries have initiated national protocols regarding developing, appraising and implementing high-quality CPGs, there remains no standardised approach to any aspect of CPG production. Methods A scoping review of the literature and document analysis were conducted according to Joanna Brigg's Institute methodology for scoping reviews. This comprised two qualitative methods: a comprehensive review of the literature (using CINAHL, Scopus and PubMeD) and a document analysis of all national and international guideline development processes (manual search of health-related websites, national/international organisational health policies and documents). Results A set of clear principles and processes were identified as crucial to CPG development, informing the planning, implementation and dissemination of recommendations. Fundamentally, two common goals were reported: to improve the quality and consistency of clinical practice (patient care) and to reduce the duplication or ratification of low-grade CPGs. Conclusions Consultation and communication between CPG working parties, including a wide range of representatives (including professional organisations, regional and local offices, and relevant national bodies) is essential. Further research is required to establish the feasibility of standardising the approach and disseminating the recommendations.